Hubungan Agama Dan Budaya Dalam Pandangan Moderasi Beragama - Marwiyatun Naimah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Institut Agama Islam Negeri Metro, 2024)
The relationship between religion and culture has become a complex topic in a variety of social and religious contexts. In the perspective of religious moderation, this relationship is seen as a balanced, respectful, and complementary interaction, where religious values do not have to conflict with cultural practices, and vice versa. Religious moderation prioritizes a middle ground attitude that emphasizes the principles of tolerance, peace, and respect for diversity. In this context, religion is not understood as a divisive force, but as a source of value that enriches the cultural life of the community. On the other hand, culture is also not interpreted as something that threatens the integrity of religious teachings, but as an expression of the social and spiritual identity of the people. This article aims to explore the understanding of how religious moderation can be a bridge in harmonizing religion with culture, as well as how religious moderation can strengthen social cohesion, enrich cultural heritage, and build harmony in a pluralistic society.